Unsteady Flow Structure on Low Aspect Ratio Wings - Rockwell, Donald (2011)
The overall objective of this investigation was to determine the quantitative flow structure on low aspect ratio wings subjected to basic classes of maneuvers, in order to provide a basis for interpretation of induced forces. Techniques of particle image velocimetry were employed for critical planes of the flow field, and a technique of stereo particle image velocimetry was developed for water-based systems. Post-processing of the acquired images allowed determination of the vorticity and streamline topology, and construction of space-time volumes of the flow structure. These approaches led to characterization of the three-dimensional flow structure on flapping wings, as well as wings in rectilinear motion, and determination of patterns of spanwise- and streamwise-oriented vorticity. Passive control in the form of a sinusoidal leading-edge, which mimics the protuberances on the flipper of the humpback whale, and active open-loop control, in the form of small-amplitude perturbations of a wing can effectively can effectively manipulate the structure of the classes of flows investigated herein. The original document contains color images.